The integration of extended reality for student-developed games to support cross-curricular learning - MacCallum, Kathryn (Frontiers in Virtual Reality, 2022)
While eXtended Reality (XR) has been shown to provide rich promise, its adoption within the educational context is still limited. Recent advances in XR technology, especially in mobile XR tools, have made XR more accessible. These advances have also enabled the development of student-created XR experiences that provide opportunities for integrating learning with technology skills development. Through the integration of critical digital skills across the curriculum, students can demonstrate a range of learning outcomes across many different learning areas. In this study, we explore how the affordances of XR can be leveraged to enable new learning opportunities, specifically in enabling students to design their own XR learning experiences. We also explore how the added context of XR games provides additional benefits to engage and motivate learners. In this article, we identify and explore twelve affordances framed in the notions of engagement, authenticity and contextualisation. These affordances have been identified in the literature to highlight the benefits of XR and were explored in terms of how the added context of student-created games leveraged these affordances. Drawing on a wider research project, we identify three scenarios that were adopted by three teachers (Mathematics, Science and Language teacher) to teach a range of subjects that drew on XR student-created games. From this analysis, we conclude with six proposed design principles that could be adopted by other teachers to guide them applying a similar approach in their teaching.